Pantun Sebagai Media Pembelajaran Sastra Daerah untuk Revitalisasi Nilai-Nilai Moral di Kalangan Generasi Muda - Ari Diana; Wiko Antoni; Susilawati Susilawati (Pusat riset dan Inovasi Nasional, 2026)
Pantun, as a form of traditional oral literature, plays a crucial role in the development of regional literature learning and character education. This study aims to analyze the application of pantun as a learning medium capable of revitalizing students' character values ​​in the modern era. The study was conducted through a literature review of several relevant scientific articles, including those by Purnama et al. (2023), Andayani (2024), Yoga (2024), and Rozani (2025), all of which discuss the relationship between pantun, learning, and character development. The analysis shows that pantun contains character values ​​such as religiosity, honesty, responsibility, courtesy, hard work, and love of country. Through pantun reciprocal activities, the creation of thematic pantun, and the integration of pantun into a local wisdom-based curriculum, regional literature learning can be an effective means of developing polite, creative, and cultured personalities. The application of pantun in the classroom not only strengthens appreciation for regional literature but also serves as a concrete strategy for revitalizing national character. Thus, pantun is no longer merely a legacy of oral tradition, but rather an instrument for moral and cultural education relevant to the needs of 21st-century education.